Children's experiences of development in alternative sports programmes. (June 2023) - Högman, Johan; Augustsson, Christian
Aim: As more children become increasingly physically inactive, efforts to reverse this negative trend are growing. Research has indicated, however, that we know relatively little about the pedagogical processes built into programmes and interventions. This is especially true in respect of how children view the process of becoming more physically active. This article therefore explores developmental processes as they unfold in the context of alternative sports programmes through children's voices. Methods: Theoretically, children's development is approached from a bioecological perspective focusing on the interaction between the child and its environment. This article builds on material collected from 5 focus groups conducted with 16 children in total (aged 11–15 years) after participating in an alternative sports programme. The data were analysed abductively using a qualitative content analysis technique. Findings: Findings illustrate how children develop physically active behaviours internally, as they acquire certain skills and knowledge, as well as between children and a multisystemic environment. In this study, children experienced that exploring practical activities in authentic situations could contribute to better understanding of the relationship between themselves and physical activities in their local community. Conclusion: To enable development in interventions, paying attention to the extent to which exo- and mesosystems influence children's relationships with the outside world is key. Participation may lead to an improved understanding of the surrounding world and the ability to further develop in an increasingly complex reciprocal process with the environment.